Key technical research of space-terrestrial integrated network based on satellite-terrestrial collaborative networking - WENG Weiwen; CHENG Jinxia; LIU Jing; LIU Shanshan; MA Ke; DENG Wei (Dianxin kexue)
With the rapid development of space-terrestrial integrated communication technologies, the satellite and terrestrial cellular communication industry ecosystems are gradually converging to meet the needs of ubiquitous broadband communication. In order to achieve efficient collaboration between satellite and terrestrial networks in terms of coverage, resources and scheduling, and improve the overall network performance, satellite-terrestrial collaborative networking will be an important direction of space-terrestrial integrated network in the future. Aiming at the goal and vision of space-terrestrial integrated network, the development status and technical challenges of space-terrestrial integrated network were explained, and the satellite-terrestrial integrated network architecture and technical system based on satellite-terrestrial collaborative deployment were proposed innovatively. The key technical schemes of satellite-terrestrial network collaboration at beam-level, service-level and planning-level were analyzed deeply, which provided guidance for the following research on satellite-terrestrial network collaboration technology.